PENYELENGGARAAN SISTEM JAMINAN SOSIAL NASIONAL OLEH BADAN PENYELENGGARA JAMINAN SOSIAL - Muhammad Ikhsan; Hilda Muliana; Sabda Wahab (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2021)
The National Social Security System is basically a state program that aims to provide protection for basic needs and social welfare for all Indonesian people in order to fulfill their basic needs for a decent life. social security to the community. BPJS is a public legal entity that administers social security and is directly responsible to the president. This means that the position of BPJS is directly under the president so that BPJS cannot be included in state-owned enterprises whose position is under the minister of SOEs or under ministries such as the ministry of health or the ministry of manpower even though BPJS is in direct contact with the two ministries. The enactment of Law Number 11 of 2020 concerning Job Creation, inserts an article related to the social security system organized by BPJS regarding the job guarantee program. BPJS in administering social security, both BPJS Health which provides health insurance and BPJS Employment which carries out employment guarantees based on social insurance. In relation to this principle, all Indonesian citizens and foreign nationals who have lived for at least 6 months in Indonesia are required to participate in this social security. The social security program organized by BPJS is a constitutional mandate, where the government is obliged to develop social security so that all Indonesian people can be guaranteed their health and socio-economic welfare.